Introduction: Law As Data, Data As Law - Barry, Brian (My University, 2024)
The datafication of law is requiring a reconsideration of approaches to legal research and education. The academy is in an uncomfortable place, with new disciplines claiming to have analytical tools to offer and to be able to replace some or all of the traditional work of lawyers and teachers. This symposium issue provides an opportunity for reflection and contains contributions that range from a call to action which embraces the new technologies, critical perspectives on the proper place of data in legal research or in governmental practices, and empirical explorations of the effectiveness of large language models. It highlights themes of diversity, rigour and engagement as key issues for lawtech scholars to bear in mind in their future work and recommends that we embrace the discomfort so that we can mature with the field.
PUBLISHED
Keywords: Digital Engagement; Digital Humanities; Judicial/Law Administration